Evidence for Bronze Age and Medieval tin placer mining in the Erzgebirge mountains, Saxony (Germany). Issue 2 (13th August 2019) - Tolksdorf, Johann Friedrich; Schröder, Frank; Petr, Libor; Herbig, Christoph; Kaiser, Knut; Kočár, Petr; Fülling, Alexander; Heinrich, Susann; Hönig, Heide; Hemker, Christiane
Abstract: Tin is an essential raw material both for the copper–tin alloys developed during the Early Bronze Age and for the casting of tableware in the Medieval period. Secondary geological deposits in the form of placers (cassiterite) provide easily accessible sources but have often been reworked several times during land‐use history. In fact, evidence for the earliest phase of tin mining during the Bronze Age has not yet been confirmed for any area in Europe, stimulating an ongoing debate on this issue. For this study, a broad range of methods (sedimentology, pedology, palynology, anthracology, OSL/14C‐dating, and micromorphology) was applied both within the extraction zone of placer mining and the downstream alluvial sediments at Schellerhau site in the upper eastern Erzgebirge (Germany). The results indicate that the earliest local removal of topsoil and processing of cassiterite‐bearing weathered granite occurred already in the early second millennium BC, thus coinciding with the early and middle Bronze Age period. Placer mining resumed in this area during the Medieval period, probably as early as the 13th century AD. A peak of alluvial sedimentation during the mid‐15th century AD is probably related to the acquisition of this region by the Elector of Saxony and the subsequent promotion of mining.